Association of gut microbiota and SCFAs with finishing weight of Diannan small ear pigs - Lan, Qun; Lian, Yuju; Peng, Peiya; Yang, Long; Zhao, Heng; Huang, Peng; Ma, Haiming; Wei, Hongjiang; Yin, Yulong; Liu, Mei (Frontiers in Microbiology, 2023)
Finishing weight is a key economic trait in the domestic pig industry. Evidence has linked the gut microbiota and SCFAs to health and production performance in pigs. Nevertheless, for Diannan small ear (DSE) pigs, a specific pig breed in China, the potential effect of gut microbiota and SCFAs on their finishing weight remains unclear. Herein, based on the data of the 16S ribosomal RNA gene and metagenomic sequencing analysis, we found that 13 OTUs could be potential biomarkers and 19 microbial species were associated with finishing weight. Among these, carbohydrate-decomposing bacteria of the families Streptococcaceae, Lactobacillaceae, and Prevotellaceae were positively related to finishing weight, whereas the microbial taxa associated with intestinal inflammation and damage exhibited opposite effects. In addition, interactions of these microbial species were found to be linked with finishing weight for the first time. Gut microbial functional annotation analysis indicated that CAZymes, such as glucosidase and glucanase could significantly affect finishing weight, given their roles in increasing nutrient absorption efficiency. Kyoto Encyclopedia of Genes and Genomes (KEGG) Orthologies (KOs) and KEGG pathways analysis indicated that glycolysis/gluconeogenesis, phosphotransferase system (PTS), secondary bile acid biosynthesis, ABC transporters, sulfur metabolism, and one carbon pool by folate could act as key factors in regulating finishing weight. Additionally, SCFA levels, especially acetate and butyrate, had pivotal impacts on finishing weight. Finishing weight-associated species Prevotella sp. RS2, Ruminococcus sp. AF31-14BH and Lactobacillus pontis showed positive associations with butyrate concentration, and Paraprevotella xylaniphila and Bacteroides sp. OF04-15BH were positively related to acetate level. Taken together, our study provides essential knowledge for manipulating gut microbiomes to improve finishing weight. The underlying mechanisms of how gut microbiome and SCFAs modulate pigs’ finishing weight required further elucidation.